GELAR MARIA SEBAGAI BUNDA ALLAH - Veerman, Glen Lukas; Kormomolin, Gerardus (Department of Theology - Sekolah Tinggi Filsafat Seminari Pineleng, 2025)
This article discusses the Catholic Church's teaching on the title of Mary as Mother of God. It demonstrates that the title of Mary as Mother of God has its basis in Scripture. In the Church's teaching tradition, especially among the Church Fathers, the title of Mary as Mother of God is also well-known. Thus, Mary, Mother of God, has deep roots in Church tradition. In the life of the Church today, this title certainly carries spiritual significance. Mary is an example for us that by trusting in God's will, God will always accompany us in facing all things. Mary became the Mother of God because, by her example to God, she accepted the task God gave her. Mary is also revered by Catholics for this example. Mary was elevated to the position of Mother of God because of her courage in carrying out the task God gave her in realizing God's work of salvation, thus God gave Mary a special place.